Ni-Catalyzed Alkene Carboacylation via Amide C–N Bond Activation - Walker, James A; Vickerman, Kevin L; Humke, Jenna N; Stanley, Levi M (Journal of the American Chemical Society, 2017)
We report Ni-catalyzed formal carboacylation of o-allylbenzamides with arylboronic acid pinacol esters. The reaction is triggered by oxidative addition of an activated amide C–N bond to a Ni(0) catalyst and proceeds via alkene insertion into a Ni(II)–acyl bond. The exo-selective carboacylation reaction generates 2-benzyl-2,3-dihydro-1H-inden-1-ones in moderate to high yields (46–99%) from a variety of arylboronic acid pinacol esters and substituted o-allylbenzamides. These results show that amides are practical substrates for alkene carboacylation via amide C–N bond activation, and this approach bypasses challenges associated with alkene carboacylation triggered by C–C bond activation.